Pedagogical content knowledge: bridging math teachers’ technology knowledge and perceived usefulness - Emmanuel Oppong-Gyebi; Francis Ohene Boateng; Yarhands Arthur Dissou (International Journal of Evaluation and Research in Education (IJERE), 2025)
The responsibility of mathematics teachers to accept technology into their instructional delivery has been a must know knowledge as professional development of Ghanaian teachers is ongoing to welcome the new standard-based curriculum by the end of 2024 at the senior high schools. This study investigated how conventional pedagogical content knowledge (PCK) influences the adoption and perceived utility of technology among mathematics teachers. Conducted with 979 mathematics teachers purposefully sampled from senior high schools in the Ashanti region of Ghana, the study employed structural equation modeling (SEM) to analyze the relationship between technology knowledge (TK), PCK, and perceived technology usefulness (PTU). The findings indicated a direct relationship between TK and PTU, with no significant mediation effect of PCK observed. Furthermore, professional experience (PE) did not moderate this relationship. However, TK was found to significantly influence PCK, thereby impacting the quality of instruction provided by teachers. Additionally, PCK was identified as a significant predictor of PTU. The study implications lies in its anticipation that Ghanaian mathematics teachers’ TK is perceived to enable them to leverage digital tools and resources effectively to connect it to their PCK, ultimately to lead to more engaging, effective, and impactful mathematics instruction delivery. This will foster meaningful learning experiences aligned with curriculum goals and learners needs.